High-resolution UAV map reveals erosional patterns and changing topography at Isimila, Tanzania - Bergstrom, Kersten; Lawrence, Austin; Pelissero, Alex; Hammond, Lauren; Maro, Eliwasa; Bunn, Henry; Musiba, Charles (My University, 2019)
Isimila is a Middle Pleistocene archaeological site located in southern Tanzania. The site is known for large surface assemblages of later Acheulean lithics such as hand axes, cleavers, scrapers, and cores. While hominin remains have yet to be discovered at the site, Isimila offers a unique window into Middle Pleistocene Homo behavior. Although Isimila has been studied extensively, the last published map of the site and surrounding area was made available in the 1970s. Here, we present an updated high-resolution map of Isimila. Data for the map were collected during aerial survey with an uncrewed/unmanned aerial vehicle (UAV). With this map, we identify new archaeological localities, erosional patterns, newly exposed geological features, and changes in site topography. The map reveals patterns of stone tool and raw material distribution that may support previous hypotheses of raw material transport into the area by hominins. This open-access map establishes a baseline for tracking changes to site topography in the future and serves as a unique tool to enable collaboration between researchers, museum personnel, and local populations to better conserve Isimila.
Keywords: Middle Pleistocene East Africa; Acheulean/Acheulian; site topography; Uncrewed/unmanned aerial vehicle; drone map